Pharmacological Treatment of Anxiety Disorders: The Role of the HPA Axis - Tafet, Gustavo E.; Nemeroff, Charles B. (Frontiers in Psychiatry, 2020)
Stress in general, and early life stress in particular, has been associated with the development of anxiety and mood disorders. The molecular, biological and psychological links between stress exposure and the pathogenesis of anxiety and mood disorders have been extensively studied, resulting in the search of novel psychopharmacological strategies aimed at targets of the hypothalamic-pituitary-adrenal (HPA) axis. Hyperactivity of the HPA axis has been observed in certain subgroups of patients with anxiety and mood disorders. In addition, the effects of different anti-anxiety agents on various components of the HPA axis has been investigated, including benzodiazepines, tricyclic antidepressant (TCAs) and selective serotonin reuptake inhibitors (SSRIs). For example, benzodiazepines, including clonazepam and alprazolam, have been demonstrated to reduce the activity of hypothalamic CRF neurons. TCAs and SSRIs are also effective anti-anxiety agents and these may act, in part, by modulating the HPA axis. In this regard, the SSRI escitalopram inhibits CRF release in the central nucleus of the amygdala, while increasing glucocorticoid receptor (GRs) density in the hippocampus and hypothalamus. The molecular effects of these anti-anxiety agents in the regulation of the HPA axis, taken together with their clinical efficacy, may provide further understanding about the role of the HPA axis in the pathophysiology of mood and anxiety disorders, paving the way for the development of novel therapeutic strategies.